2022
DOI: 10.1155/2022/6357893
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Lovage under Exposure of Light-Emitting Diode Illumination and Analysis of Rutin Produced by High Performance Liquid Chromatography (HPLC) and Ultraviolet-Visible Spectroscopy (UV-Vis)

Abstract: To meet the requirements of a sustainable agricultural economy such as quality, resource conservation, and efficiency, the interaction between the cultivation parameters of plants and the resulting plant ingredients are becoming more and more interesting, especially regarding secondary metabolites. Therefore, the cultivation of lovage under the influence of light-emitting diode illumination and controlled environment conditions was studied and data on the rutin concentrations obtained are presented. Different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…With respect to our study from 2022, where no clear significance could be shown between the effect of two green light proportions (20 and 40% of the total PPFD) on rutin content, the presented work investigated the potential effect of lower green light proportions (Wack et al, 2022). The results indicate that green light as a sole factor does not have a significant effect, even at low levels.…”
Section: Rutin Contentmentioning
confidence: 71%
See 2 more Smart Citations
“…With respect to our study from 2022, where no clear significance could be shown between the effect of two green light proportions (20 and 40% of the total PPFD) on rutin content, the presented work investigated the potential effect of lower green light proportions (Wack et al, 2022). The results indicate that green light as a sole factor does not have a significant effect, even at low levels.…”
Section: Rutin Contentmentioning
confidence: 71%
“…In our review from 2020, we point out partially contrary results of the effect of various light treatments on flavonoid content, even for plants belonging to the same family or variety (Thoma et al, 2020). Based on our results from 2022 regarding rutin content in lovage (Levisticum officinale W.D.J KOCH), no clear significant effect of specific wavelength components could be shown (Wack et al, 2022). No significant difference between two Thoma et al 10.3389/fsufs.2023.1322443 Frontiers in Sustainable Food Systems 02 frontiersin.org relatively high proportions of green light (20 and 40% of the total photosynthetic photon flux density (PPFD)) where shown.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation